ALK-Negative Anaplastic Large-Cell Lymphoma Diagnosed on Liver Biopsy in a Child Presenting with Nonresolving Pyrexia - Kakkar, Aanchal; Sharma, Bhavna; Das, Prasenjit; Jain, Siddharth; Dattagupta, Siddharth; Sood, Rita (Indian Journal of Medical and Paediatric Oncology, 2019)
ALK-negative anaplastic large-cell lymphoma (ALCL) is a rare non-Hodgkin lymphoma occurring in adulthood. We report a case of a 13-year-old boy who presented with a 6-month history of fever with jaundice and pancytopenia. Computed tomography abdomen showed multiple hypodense lesions in the liver. Bone marrow biopsy revealed necrotizing granulomas. The patient was treated with antitubercular treatment but failed to show a response. Liver biopsy performed subsequently showed features of ALK-negative ALCL. Extranodal involvement in ALK-negative ALCL can have unusual clinical presentations. This case highlights the utility of timely tissue diagnosis in patients with nonresolving pyrexia and organ lesions on imaging.
Keywords: ALK-negative; anaplastic large-cell lymphoma; extranodal; liver biopsy; lymphoma